Effect of Depth of Flooding on the Rice Water Weevil, Lissorhoptrus oryzophilus, and Yield of Rice - Tindall, Kelly V. (University of Wisconsin Library, 2013)
The rice water weevil, Lissorhoptrus oryzophilus (Kuschel) (Coleoptera: Curculionidae), is a semi-aquatic pest of rice and is the most destructive insect pest of rice in the United States. Adults oviposit after floods are established, and greenhouse studies have shown that plants exposed to deep floods have more eggs oviposited in leaf sheaths than plants exposed to a shallow flood. Experiments were conducted in three mid-southern states in the USA to determine if the depth of flooding would impact numbers of L. oryzophilus on rice plants under field conditions. Rice was flooded at depths of approximately 5 or 10 cm in Arkansas in 2007 and 2008 and Louisiana in 2008, and at depths between 0–20 cm in Missouri in 2008. Plants were sampled three and four weeks after floods were established in all locations, and also two weeks after flood in Missouri. On all sampling dates in four experiments over two years and at three field sites, fewer L. oryzophilus larvae were collected from rice in shallow-flooded plots than from deep-flooded plots. The number of L. oryzophilus was reduced by as much as 27% in shallow-flooded plots. However, the reduction in insect numbers did not translate to a significant increase in rice yield. We discuss how shallow floods could be used as a component of an integrated pest management program for L. oryzophilus.